The Middle to Late Triassic of Central Saudi Arabia with emphasis on the Jilh Formation. Part I: lithostratigraphy, facies and paleoenvironments, palaeontology and biostratigraphic age calibration from outcrop studies - Le Nindre, Yves-Michel; Vaslet, Denis; Vrielynck, Bruno; Krystyn, Leopold; Manivit, Jacques; Memesh, Abdullah; Davies, Roger Brett (Comptes Rendus. Géoscience, 2023)
The Middle to Late Triassic (Anisian–Carnian) Jilh Formation crops out along an approximately 880 km belt in Central Saudi Arabia to the east of the Proterozoic Arabian Shield. This outcrop belt has been mapped, described and analysed in detail, first by geologists of the BRGM (1990–1991) and more recently by the present authors. The current synthesis, which includes the results of previous comprehensive analyses of the overlying Norian to Early Jurassic Minjur Sandstone/Formation in outcrop and subsurface locations, is being published in two parts. The first part (Part I) consolidates previous sedimentological and biostratigraphic analyses, and introduces new stratigraphic results provided by conodonts and ammonoid studies. Part II “Sequence stratigraphy, depositional and structural evolution, and regional correlations” exploits the results of Part I, providing a dynamic reconstruction and a renewed vision of the Middle to Late Triassic at the regional scale.The Jilh Formation at outcrop consists of a multilayer system of thinly bedded, mixed siliciclastics with subordinate carbonates and evaporites, representing non-marine to offshore settings. Individual beds are difficult to correlate at regional scale. A pre-existing outcrop-based, three-fold, sub-division of the Jilh Formation into lithological units is shown to cross timelines and cannot be used as the basis for regional correlation. Instead, new identifications of Middle and Late Triassic conodonts in the formation and at the base of the overlying Minjur Sandstone/Formation, allied to re-interpretation of previously described ammonoids, provide new paleogeographic and chronostratigraphic data, which improve our understanding of transgressive–regressive (T–R) sequences at the outcrop and platform scales and demonstrate that the lithostratigraphic units of the Jilh Formation were inconsistently recognized at outcrop north of 25°30$^{′ }$N due to erosion by a fourth unit of early Alaunian (Middle Norian) age; this raises the issue of the Jilh–Minjur boundary addressed in Part II. Marine flooding events are indicated by tidal flat sediments during the Anisian, and thin carbonate beds during the Ladinian, late Julian (Early Carnian), associated with Fe-oolite beds, and Tuvalian (Late Carnian). We recognise a regional Carnian–Norian hiatus and an early Middle Norian transgression, as well as marine and continental erosional discontinuities affecting the stacking pattern of the T–R wedges. These observations and analyses provide a sound foundation for sequence stratigraphic analysis and regional correlation, which are the subjects of Part II.